Pergolakan Timor-Timur 1999 dan Relevansinya pada Penerapan Hak Asasi Manusia di Indonesia - Sila, Urbanus; Yustinus, Yustinus (Universitas Tanjungpura, 2024)
This article focuses on the role of the Indonesian State in fighting human rights violations during the 1999 East Timor Upheaval. The 1999 East Timor Upheaval was one of the most serious human rights violations that occurred in Indonesia. The Indonesian state has an important role in eradicating human rights violations that occurred in East Timor in 1999, namely by carrying out investigations and trials against perpetrators of human rights violations, providing compensation to victims of human rights violations, and reforming military security law. The method used in this paper is qualitative research through a literature review. Primary sources from books and articles. The Indonesian state needs to increase its role in eradicating human rights violations during the 1999 East Timor Upheaval by holding trials for perpetrators of serious human rights violations, providing adequate compensation to victims of human rights violations, carrying out reforms in the security and military sector, and implementing reforms in the security and military sector. consistently and sustainably, as well as providing education to the community. about the importance of human rights and preventing human rights violations. By taking these steps, the Indonesian state can demonstrate its commitment to fighting human rights violations and protecting the human rights of all its citizens.